Improving the peak‐to‐average power ratio of the single‐carrier frequency‐division multiple access system through the integration of tone injection and tone reservation techniques. (7th September 2017) - Chen, Houshou; Liang, Hsin‐Ying; Chu, Hung‐Chi; Lin, Chuan‐Bi
Summary: This paper proposes a new method for reducing the peak‐to‐average power ratio of the single‐carrier frequency‐division multiple access system. The method is an integration of the tone injection (TI) and tone reservation (TR) techniques. A recommended method that uses TI to improve TR's low data transmission rate problem that is caused by the reservation of subcarriers. Additionally, to reduce the massive amount of computation required by the combined needs of TI and TR, an iterative flipping algorithm was adopted for this purpose. Simulation results indicate that the proposed method is not only capable of effectively improving the peak‐to‐average power ratio–reduction efficiency of the single‐carrier frequency‐division multiple access system but it can also improve the data transmission rate of the conventional TR technique. Abstract : This paper proposes a new method for reducing the peak‐to‐average power ratio of the single‐carrier frequency‐division multiple access system. The method is an integration of the tone injection (TI) and tone reservation (TR) techniques. A recommended method that uses TI to improve TR's low data transmission rate problem that is caused by the reservation of subcarriers. Additionally, to reduce the massive amount of computation required by the combined needs of TI and TR, an iterative flipping algorithm was adopted for this purpose.